Doing sport online? Managing sport training during COVID-19 - Borghi, G.; Caire, M.; Ferrero Camoletto, R. (Italian Sociological Review, 2021)
The Covid-19 pandemic has provided an unparalleled experience of disruption of individual everyday routinary lives as well as of societal organization. Sport as a field of practices and as an economic sector has been strongly affected by the lockdown as a global response, suffering from the shutdown of competitive sports at all levels and from the postponement of mega-events. Within these hard times, imposing strong limitations to the possibility for athletes and the general population to move around, work out and socialize, sport workers were compelled to come up with new ways to make people exercise: one of the solutions adopted has been by using social media and online platforms to host training activities.In this article we will analyze data from an online survey involving coaches, athletic trainers and other sport workers from three sport sub-fields: a team sport, basketball; an individual sport, tennis; and a wide array of activities, the fitness and wellness world. We will focus on the impact of "going online" in those three sport subfield, exploring the different attitudes and practices adopted to adjust sport training by providing exercising through online communication devices without physical co- presence.